Abnormal quiet day variations in Indian region along 75 E meridian - Bhardwaj, S. K.; Rao, P.B.V. Subba; Veenadhari, B. (My University, 2015)
The present study mainly focuses on the anomalous characteristics observed in some abnormal quiet day (AQD) variations of the north–south (H) and east–west (D) components of geomagnetic field at 11 Indian stations for the years 2004, 2005, and 2009 during low solar activity period for summer and winter months. In this study, during some quiet days, horizontal component (H) at stations situated near equator to the Sq focus latitudes has shown double peak structure, exhibiting maximum in the forenoon and afternoon hours. Correspondingly, declination component (D) over the low latitudes has shown features outside the normal trend, i.e., westward-directed field in the morning hours and eastward-directed field in the afternoon hours and shows negative bay-type of variations. The technique of principal component analysis (PCA) has been applied to the data sets for presenting a quantitative estimate of the influence of day-to-day variability in the Sq current system on normal (NQD) and abnormal quiet (AQD) days. AQDs observed at the Indian stations are reflected in the second principal component PC-2. Anomalous changes in day-to-day variations (H and D) are interpreted as an influence of high latitude magnetospheric current systems as well as due to single current vortex (SCV) located in the ionosphere whose focus lie between 10 and 15 N geomagnetic latitude for the northern hemisphere winter AQDs.
Keywords: Quiet day variations